Space Systems Design for Research on the Interaction of Osteoblast-like Cells and Biomaterials (Hydroxyapatite Particles and Titanium) in Microgravity Environment. (2015) - Carnio, Martina; Massimiani, Chiara; Piperni, Sara Gemini; Zambuzzii, Willian; Cappelletti, Chantal; Graziani, Filippo
Abstract: Microgravity and ionizing radiations are some of the special condition that characterize the space environment. These conditions cause major changes in human bodies, or in biomedical samples; in particular, the bone tissue in microgravity conditions, lack of mechanical loading which is one of the main stimulus to bone remodelling needed, loose elasticity and toughness. In 2014 a cooperation between GAUSS srl. (Group of Astrodynamic for the Use of Space System, Rome, Italy), the University of Brasilia (UnB, Brasilia, Brazil) and the State University of São Paulo (UNESP, Botucatu, São Paulo, Brazil) has been started to study in orbit the effects of the exposure of osteoblast-like cells, responsible to forming-up a new bone, to gold standard biomaterials (hydroxyapatite particles and titanium). Biomaterials are artificial materials, with potential biocompatibility. They are more used in regenerative medicine to support cells behaviour to repair the damage. Nowadays, this field of medicine requires collaboration among engineers, biologists, chemists to create and test new biomaterials and to investigate what might be the best to use to enhance the performance during the repair of the damage. By now, in a field so critical to human health and biomaterial development, it is very important to explore and exploit new research pathways and hence, it is clear that the exposition of osteoblast-like cells to biomaterials under reduced gravity conditions certainly will induce changes in cell adhesion, growth and differentiation of those cells. Each experiment will use the microgravity environment to conduct experimentation that could produce tremendous health benefits for humankind such as advancements in biomaterial screening, tissue engineering/regeneration, cell replacement therapy. Therefor the main goal of this project is to investigate potential effects of the space environment exposure on osteoblast-like cells and biomaterials through an autonomous space system, designed and manufactured specifically for this goal. Specifically, this paper describes the engineering solutions to design and manufacturing autonomous space system that can allow to keep alive and to study these kinds of cells.